2009
DOI: 10.2478/s11696-008-0085-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of hydrocolloids as baking improvers

Abstract: Hydrocolloids (or gums) belong to a group of biopolymers widely used in food technology. In the bakery industry, these compounds help to improve food texture and moisture retention, to retard starch retrogradation, and, finally, to enlarge the overall quality of the products during storage. Since recently, some hydrocolloids are being used due to their polymeric structure as fat replacers to obtain low calorie products and to substitute gluten in the formulation of gluten-free breads. This study describes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 67 publications
1
65
0
Order By: Relevance
“…These molecular interactions eventually led to the formation of AA. Most of the hydrocolloids mentioned above have been used to modify the texture of various food products by functioning as gelling or thickening agents (Kohajdova & Karovicova, 2009). Therefore, the various modulating activities in AA formation, observed for the different hydrocolloids, might be due to their different effectiveness in interfering with the above molecular interactions.…”
Section: Effects Of Hydrocolloids On Acrylamide Formation In Model Symentioning
confidence: 99%
See 1 more Smart Citation
“…These molecular interactions eventually led to the formation of AA. Most of the hydrocolloids mentioned above have been used to modify the texture of various food products by functioning as gelling or thickening agents (Kohajdova & Karovicova, 2009). Therefore, the various modulating activities in AA formation, observed for the different hydrocolloids, might be due to their different effectiveness in interfering with the above molecular interactions.…”
Section: Effects Of Hydrocolloids On Acrylamide Formation In Model Symentioning
confidence: 99%
“…Hydrocolloids are hydrophilic polymers that can modify the functional properties of aqueous food systems, such as thickening, gelling and emulsifying properties (BeMiller, 2008;Kohajdova & Karovicova, 2009). Studies showed that the addition of certain hydrocolloids to food systems could enhance water retention (Albert & Mittal, 2002;Pedroso & Demiate, 2008;Ramos, Farias, Almada, & Crivaro, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…According to Kohajdová & Karovičová (2009), Na CMC is widely used in bakery industry for improving product structural consistency, maintaining moisture, and improving the mouth-feel of bakery products. Mohammadi et al (2014) reported that increase in Na CMC concentration in gluten-free flat bread yielded bigger gas cells, leading to better crumb porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account their ability to improve the technological and sensory properties of gluten‐free doughs, hydrocolloids can also find a good job in improving the quality of durum wheat bread in which the addition of vegetable flours involves significant changes in the structure (Rojas et al. , 1999; Kohajdovà & Katovicòvà, 2009).…”
Section: Introductionmentioning
confidence: 99%